Energy metabolism and tissue respiration in patients with obstructive sleep apnoea hypopnoea syndrome - Soltani, R. E. (Journal of Education, Health and Sport, 2020)
A comparative study of the features of energy metabolism and tissue respiration in patients with obstructive sleep apnoea hypopnoea syndrome during the day and at night was performed. It has been established that during the day in the patients with OSAHS energy metabolism is higher than normal basal metabolism; in this case the cardiovascular system transports more oxygen and its tissues extract more than in norm. At night, due to cyclic attacks of apnoea hypopnoea, the release of sympathetic nervous system mediators is stimulated, as a result the intensity of tissue respiration also increases significantly and oxygen delivery is activated mainly by cardiovascular system. Such mechanisms are crucial for development of hypertension in the patients with OSAHS.